Perancangan Sistem Presensi Siswa Berbasis Web Menggunakan Notifikasi API WhatsApp - Tanjung, Muhammad Ridho; Annas, Firdaus; Darmawati, Gusnita; Yuspita, Yulifda Elin (Yayasan Lembaga Studi Makwa, 2023)
The aim of this article is to produce a design for a web-based student attendance system using the Whatsapp API at MTs Negeri 7 Agam. Currently, the attendance process at MTs Negeri 7 Agam is still manual, making the use of paper for the attendance register less efficient. Apart from that, recapitulation of student attendance is also done manually and takes a long time. With this system, it can make it easier for teachers to carry out attendance and also recapitulation, so that teachers can easily get the data they want. This research uses the development method or Research and Development (R&D). Using the RAD (Rapid Application and Development) development model. The product tests used in this research are validity tests, practicality tests, and effectiveness tests. The findings from this research are that a web-based student attendance system has been successfully designed and can be used to support monitoring of student arrival and attendance at a school. The results of the product validity test with two experts in the field of programming and one expert in the field of linguistics obtained a value of 0.92, the results of the practicality test with twenty teachers at MTs Negeri 7 Agam obtained a value of 0.74, categorized as a high level of practicality. , and the results of the effectiveness test with 30 students and 5 parents obtained a value of 0.92, categorized as a very high level of effectiveness. So from these results, the Web-Based Student Attendance product using the WhatsApp API at MTs Negeri 7 Agam is valid, practical and effective to uses. Abstrak Tujuan artikel ini untuk menghasilkan sebuah rancangan sistem presensi siswa berbasis web dengan menggunakan API Whatsapp di MTs Negeri 7 agam, saat ini proses presensi di MTs Negeri 7 agam masih manual, menyebabkan pemakaian kertas untuk daftar hadir kurang efesien. Selain itu rekapitulasi presensi siswa juga dilakukan secara manual dan memakan waktu yang lama. Dengan adanya sistem ini dapat memudahkan guru dalam melakukan presensi dan juga rekapitulasi, sehingga para guru mudah mendapatkan data yang di inginkan. Penelitian ini menggunakan metode pengembangan atau Research and Development (R&D). Menggunakan model pengembangan RAD (Rapid Aplication and Development). Uji produk yang digunakan dalam penelitian ini adalah uji validitas, uji praktikalitas, dan uji efektivitas. Temuan dari peneletian ini adalah membuat sebuah sistem presensi siswa berbasis web telah berhasil dirancang dan dapat digunakan sebagai penunjang monitor kedatangan dan kehadiaran siswa pada sebuah sekolah. Hasil uji validitas produk dengan dua orang ahli di bidang pemrograman dan satu orang ahli di bidang kebahasaan diperoleh nilai 0,92, hasil uji praktikalitas dengan dua puluh orang bapak/ibuk guru di MTs Negeri 7 Agam diperoleh nilai 0,74 dikategorikan dengan tingkat kepraktisan tinggi, dan hasil uji efektivitas dengan 30 orang siswa dan 5 orang tua diperoleh nilai 0,92 dikategorikan dengan tingkat keefektifan sangat tinggi. Maka dari hasil tersebut, produk Presensi Siswa Berbasis Web Dengan Menggunakan API Whatsapp di MTs Negeri 7 agam sudah valid, praktis, dan efektif untuk digunakan.